Medical comorbidities and other factors associated with migraine among individuals with diabetes mellitus in Hungary: a cross-sectional study using European Health Interview Surveys 2009–2019 - Varga, Eszter; Ghanem, Amr Sayed; Faludi, Eszter; Nguyen, Chau Minh; Kovács, Nóra; Nagy, Attila Csaba (Frontiers in Endocrinology, 2024)
Introduction: Migraine, a debilitating neurological disorder characterized by recurrent headaches, affects over 1.1 billion individuals globally. Diabetes mellitus (DM), a chronic metabolic condition marked by high blood sugar levels, affects 463 million individuals according to the International Diabetes Federation. Our study aimed to evaluate the association between migraine and DM and to identify several demographic, socioeconomic, and lifestyle factors, as well as medical and psychiatric comorbidities, associated with migraine among individuals with DM. Methods: This cross-sectional study is based on data from the European Health Interview Surveys conducted in 2009, 2014, and 2019 in Hungary. Pearson’s chi-squared tests and multiple logistic regression models were used to assess associations. Statistical significance was set at p<0.05. Results: In multiple regression analyses, we found no significant association between DM and migraine after adjusting for socioeconomic status, various health conditions, and lifestyle factors (OR=0.84, 95% CI: 0.66-1.06). However, adults with DM who had comorbid conditions including stroke (OR=2.08, 95% CI: 1.06-4.08), low back pain (OR=3.52, 95% CI: 2.13-5.84), and depression (OR=4.91, 95% CI: 2.84-8.47) were significantly more likely to suffer from migraine. Discussion: Our study found no significant difference in the prevalence of migraine among adults with and without diabetes mellitus. However, several comorbidities were found to be significantly associated with migraine occurence in those with DM. Thus, the study’s results highlight the need for proper management of diabetes, especially in terms of comorbidities, to mitigate migraine risk factors and improve patient outcomes.